2010
DOI: 10.1002/ar.21203
|View full text |Cite
|
Sign up to set email alerts
|

The Global Impact of Sutures Assessed in a Finite Element Model of a Macaque Cranium

Abstract: The biomechanical significance of cranial sutures in primates is an open question because their global impact is unclear, and their material properties are difficult to measure. In this study, eight suture-bone functional units representing eight facial sutures were created in a finite element model of a monkey cranium. All the sutures were assumed to have identical isotropic linear elastic material behavior that varied in different modeling experiments, representing either fused or unfused sutures. The values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 76 publications
3
68
2
Order By: Relevance
“…However, the results are at variance with experimental and modelling studies on mammals that suggest some regions of the mammalian skull experience only very low strains during mastication [31,80]. Similarly, computer models of mammal skulls with some patent sutures do not differ significantly from skulls with no (or completely fused) sutures [52]. However, further discussion must await the analysis of a comparable mammalian skull with a full complement of patent sutures.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the results are at variance with experimental and modelling studies on mammals that suggest some regions of the mammalian skull experience only very low strains during mastication [31,80]. Similarly, computer models of mammal skulls with some patent sutures do not differ significantly from skulls with no (or completely fused) sutures [52]. However, further discussion must await the analysis of a comparable mammalian skull with a full complement of patent sutures.…”
Section: Discussionmentioning
confidence: 88%
“…However, Wang et al . [52] concluded that patent sutures have little effect on skull strains in primates, and that they are perhaps less important mechanically than in animals with more patent sutures or a greater suture to bone volume, such as lizards and alligators [24,53]. Such studies combined with experimental data provide important information on suture form and function [3,23,29,30,32,54], but for a full overview of the impact of patent and fused sutures on load transfer within the skull more comprehensive analyses are necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides being important loci of craniofacial growth (Opperman, 2000), sutures are mechanically “imperfecta” in an otherwise rigid body (a cranium), and their mechanical impact has been often discussed and investigated using various experimental and computer-aided techniques in both living and fossil species (Behrents et al, 1978; Bright and Gröning, 2011; Farke, 2008; Herring, 1993; Herring and Mucci, 1991; Herring and Rafferty, 2000; Herring and Teng, 2000; Jasinoski et al, 2010a,b; Jaslow and Biewener, 1995; Kupczik et al, 2009; Kupczik et al, 2007; Lieberman et al, 2004; Moazen et al, 2009a,b; Oudhof and Van Doorenmaalen, 1983; Porro et al, 2011; Rafferty and Herring, 1999; Rafferty et al, 2003; Rayfield, 2004; 2005; Reed et al, 2011; Smith and Hylander, 1985; Sun et al, 2004; Wang et al, 2008, 2010a). Experimental studies (Behrents et al, 1978; Herring and Mucci, 1991; Herring and Teng, 2000) have demonstrated that patent sutures affect strains locally (i.e., near the suture), but practical considerations limit the ability of purely experimental studies to assess the global influence of these joints across the entire cranium.…”
Section: Introductionmentioning
confidence: 99%
“…Most finite element studies involving cranial sutures use static loading conditions and assume linear elastic behaviour of the suture material (e.g., Jasinoski et al, 2010aJasinoski et al, , 2010bMoazen et al, 2009;Wang et al, 2010). However, the computational investigation by Tanaka et al (2000b) of time-dependent response in a rat suture assumed the material to be linear viscoelastic.…”
Section: Introductionmentioning
confidence: 99%